BISPHENOL A DOSE- AND TIME-DEPENDENTLY INDUCES OXIDATIVE STRESS IN RAT LIVER MITOCHONDRIA EX VIVO - Dutta, Mousumi; Paul, Goutam (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The probable toxic effects of bisphenol A (BPA) on different physiological functions have been reported in animal models. The role of BPA in mitochondrial oxidative stress has not been reported till date. The present study is aimed to elucidate dose- and time-dependent oxidative stress generation by BPA, respectively, in rat liver mitochondria in ex vivo model. Methods: The incubation mixture of BPA-treated groups containing mitochondria, 50 mM potassium phosphate buffer (pH 7.4), and different concentrations of BPA (20â€“160 Î¼M/ml) (dissolved in 12% DMSO) in a final volume of 1.0 ml was incubated at 37Â°C in incubator for different time durations (30 minâ€“2 h). Whereas, the incubation mixture of control group contained DMSO (12%), mitochondria and 50 mM potassium phosphatebuffer (pH 7.4).’ will be replaced by â€˜Whereas, the incubation mixture of control group contained the same constituents except BPA. Result: We have observed significant decrease in mitochondrial intactness incubated with BPA in dose- and time-dependent manner under bright field and confocal microscopic study compared to control. Further, we have observed a decrease in mitochondrial reduced glutathione (GSH) content and increase in lipid peroxidation and protein carbonylation levels in dose- and time-dependent manner in BPA-exposed mitochondria. We have found a significant increase in the activity of Mn-superoxide dismutase and decrease in the activities of GSH peroxidase, GSH reductase, pyruvate dehydrogenase, and other three enzymes of Kreb’s cycle dose and time dependently in BPA-exposed mitochondria. The results indicate that exposure to BPA leads to decrease in intactness of mitochondria and increase in oxidative stress in mitochondria isolated from rat liver in a dose- and time-dependent manner. Conclusion: It can be concluded that the incubation of mitochondria isolated from rat liver with BPA, caused oxidative stress-mediated damages in mitochondria in both dose- and time-dependent manners.